REKAYASA PERANGKAT LUNAK APLIKASI INVENTARIS BARANG PADA BADAN USAHA MILIK DESA (BUMDES) BINA MADANI DESA DASAN LEKONG: Yuliadi, Rodianto, M. Julkarnaen - Yuliadi Idrus; Rodianto Rodianto; M. Julkarnaen (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2021)
A computer-based system is an absolute necessity that a government and private agency must have in managing data and obtaining information quickly and accurately. Village-Owned Enterprises (BUMDes) Bina Madani in managing inventory data and delivering information to the public related to BUMDes information is still done manually, so that some people do not know BUMDes activities. Therefore, it is necessary to design an application that can be used by BUMDes managers in managing inventory data and delivering information on BUMDes activities to the public. The BUMDes data management application is made with PHP programming and MySQL database and the development method uses the prototype method. With this application, it makes it easier for BUMDes administrators to process inventory data and improve services in marketing businesses managed by BUMDes.